The Curiosity of Madeleine Hachard: Ursuline Missionaries and the Company of the Indies in Colonial Louisiana - Kostroun, Daniella J. (The catholic historical review, 2024)
This article proposes that the printed letters attributed to Madeleine Hachard (Rouen, 1728), one of the founding mothers of the Louisiana Ursulines in 1727, are a parody and not authentic primary sources as commonly thought. Drawing on new archival evidence and the methodologies of cultural history, literary analysis, and book history, it posits that an anonymous parodist purloined letters sent to France by other Ursulines, altered them, and then published them falsely under Hachard’s name. The parodist’s motive was to use the eighteenth-century trope of the ingénue to critique the disruptions of the Law System (also known as the “Mississippi Bubble”) (1718–1720) to the French Church.